American studies - McDowell, Tremaine, 1893-1959 (University of Minnesota Press, 1948)
Although the immediate subject of this book is American Studies, its ultimate concern is with the broad pattern of higher education in the United States. The program of American Studies uses the materials of the American scene to advance a contemporary m.